Biomechanical evaluation of four internal fixation systems for two-segment anterior cervical corpectomy and fusion: a finite element analysis - Yuan, Wei; Pei, Lei; Wang, Han; Liu, Yicheng; Kang, Ruohan; Zhu, Yue (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAnterior cervical corpectomy and fusion (ACCF) is a key surgical intervention for cervical spine pathologies, but multi-segment ACCF is associated with high risks of instability, implant failure, and adjacent segment degeneration (ASD). Conventional internal fixation system, vertebral body screw (VBS), titanium plate (TP), combine with titanium mesh cage (TMC) have limitations such as insufficient three-column fixation. Anterior transpedicular screws (ATPS) and 3D-printed artificial vertebral bodies (3D-AVB) have shown potential to improve biomechanical performance, but direct biomechanical comparisons of different internal fixation system systems in two-segment ACCF remain lacking.MethodsA finite element (FE) model of the C1-T1 cervical spine was constructed and validated. Four two-segment ACCF (C5-C6 corpectomy) models with different internal fixation systems were established: (1) Group 1: four VBS with TP and TMC; (2) Group 2: four oblique VBS with 3D-AVB; (3) Group 3: two superior VBS and two inferior ATPS with 3D-AVB; (4) Group 4: four ATPS with 3D-AVB. A 73.6 N axial load and 1.0 Nm moment were applied. Outcome measures included range of motion (ROM) of surgical (C4-C7) and adjacent segments, maximum von Mises stress of implants, bone-implant interfaces, and adjacent intervertebral discs.ResultsAll four groups reduced C4-C7 ROM, with Group 4 showing the most significant reduction (≈98% for flexion/extension), followed by Group 3, Group 2, and Group 1 (68.5% flexion reduction). Group 4 exhibited slightly increased adjacent segment ROM (54.8% increase in C3-C4 extension). Implant stress was lowest in Group 4 (54.8 MPa) and highest in Group 2 (255.8 MPa). Group 4 also had the lowest bone-implant interface stress at C4 and T1, whereas Group 2 had the highest. Adjacent disc stress in Group 4 was comparable to the intact model, while other groups showed increases (46.9% in Group 1).ConclusionThe Group 4 (4 ATPS + 3D-AVB system) is preferred for two-segment ACCF, as it provides superior surgical segment stability, reduces stress on implants, bone-implant interfaces, and adjacent discs. For cases where Group 4 is inapplicable, alternatives should be prioritized as follows: Group 3 (2 VBS +2 ATPS + 3D-AVB), Group 2 (4 oblique VBS + 3D-AVB), and Group 1 (4 VBS + TP + TMC). Long-term efficacy of these systems requires verification via future clinical trials.